Digital Transformation, Sustainability, and Strategic Evolution in Marketing Management Strategies: : A Bibliometric Review of Trends and Trajectories (1990–2025) - Joni Kutu' Kampilong; Ferdy Rumambi; Silvya Mandey; Agus Soegoto; Christy Rondonuwu (SOSIOEDUKASI, 2025)
This study is a bibliometric literature review of trends and paths in marketing management strategies between 1990 and 2025, which integrates 683 peer-reviewed articles to trace the intellectual development of the topic. We used VOSviewer to examine the existence of keywords and the cooperation of countries. The common topic groups that we identified included five aspects: AI-driven marketing, digital transformation, sustainability, consumer behavior in the digital environment, and methodological reflexivity. The findings indicate that the number of publications has grown significantly since 2005, and thinking has changed significantly. Integrated, technology-based, and ethically conscious product models have replaced traditional product models. Digital and AI-based marketing are highly mature, while the integration of sustainability is still new, particularly in developing economies. Scholars and professionals tend to collaborate in online environments; however, ethical regulations, longitudinal research, and the inclusion of geography remain issues. Geographic cooperation is still geographically concentrated in North America, Europe, and East Asia, which makes the whole world less representative. The added value of this review is the explanation of the stages of adoption, interdisciplinary convergence, and outlining the gaps in research that should be given the highest priority, especially within ethical AI, digital sustainability interaction, and situation-specific strategy implementation. The results provide useful theoretical proposals and practical recommendations for scholars and practitioners in the dynamic environment of future-ready marketing strategies.